Laparoscopy and computed tomography imaging in advanced ovarian tumors: A roadmap for prediction of optimal cytoreductive surgery - Ahmed Samy El-Agwany (Wolters Kluwer Medknow Publications, 2018)
Introduction: Comprehensive staging laparotomy and cytoreductive surgery followed by chemotherapy has been the standard of care in advanced ovarian cancer. Neoadjuvant chemotherapy is an alternative in inoperable advanced cases. To select patients amenable for successful cytoreduction, major determinants including CT imaging and laparoscopy could be of value. There is no general accepted model for selection and reproducibility of techniques are a major challenge due to different clinical practice and complexity of scoring systems. Some lesions as small size (<5 mm) peritoneal deposits and mesenteric affection are hard to see on CT so, complementary laparoscopy may play a role in the preoperative assessment. The aim of this study was evaluation of the role of laparoscopy in advanced ovarian tumors for prediction of optimal cytoreductive surgery in relation to CT and surgical peritoneal carcinomatosis index (PCI). Aim: Was to evaluate laparoscopic assessment in advanced ovarian tumors for prediction of optimal cytoreductive surgery in relation to CT and surgical peritoneal carcinomatosis index (PCI). Setting: Gyne-oncology specialized center, El-Shatby maternity university hospital, Alexandria Egypt. Methods: From January 2016 to December 2016, 15 patients were recruited from gyne-oncology specialized center, Alexandria, Egypt. Patients underwent a special design described later then laparoscopy using palmar point entry was done for assessing small lesions and the extent of affection in surface peritoneal, mesentery, serosa of the gut especially small intestine (terminal ileum affection, more or less than 50% affection) mainly with evaluating other sites as liver surface and diaphragm peritoneal surface affection after removal of ascites by aspiration. Findings were correlated with laparotomy and CT scan findings. Surgery was performed in the same setting which is better or with in two weeks. Results: There were two cases with upper abdominal surgeries (cholecystectomy and splenectomy) where no visualization of liver and stomach on laparoscopy but were free on CT scan and surgical evaluation. Douglas pouch was not assessed in two patients with large fixed bilateral ovarian masses on laparoscopy. Two cases with diaphragmatic affection on CT scan related to the posterior surface were not detected on laparoscopy. These findings were correlated with surgical findings as the gold standard. The pathology was ranging from low grade to high grade serous cyst adenocarcinoma. Conclusions: Laparoscopic evaluation is a useful adjunct with CT prior to performing ovarian cancer cytoreductive surgery for assessment of operability. Laparoscopy is better for evaluating extent of serosal affection in advanced tumors in cases with omental cakes on CT. A roadmap for prediction of operability in advanced ovarian cancer can be used by combing CT PCI and laparoscopic assessment.